EFFECT OF SOME SOIL PROPERTIES ON IRON SORPTION - & et al., Jar Allah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Laboratory experiment was carried out in order to study the adsorption of Fe as FeEDDHA as related to some soil properties in six calcareous soils from the middle of Iraq. Langmuir, Freundlich and Temkin equations were used for describing Fe adsorption. The best equation was chosen according to highest value of r, r2 and t and least value of Standard error of estimate. The results showed that Freunglich equation was more efficient for describing Fe sorption compared with other physicochemical equations used, depending on highest values of, r (0.985), r2 (0.970) and t ( 20.01) and lower standard error SE.e (0.186). Maximum adsorption capacity in tested soils were 415.2, 393.7, 353.7, 344.2, 318.4 and 306.0 µg Fe g-1soil while the binding strength were 0.059, 0.046, 0.059, 0.051, 0.059 and 0.064 ml Fe µg-1 for Balad, Al-Khalis, Al-Raaid, Al-Wehda, Al-Mussayib and Al-Rashidaaa. 59.2% of the applied Fe was sorbed on soil while 40.8% remained soluble in soil solution. Freunglich adsorption constants (lnKf and 1/n) significantly correlated with Langmuir maximum adsorption (b) and binding strength (K). Also, the maximum adsorptive capacity (b) of Langmuir models statistically related to soil properties (EC, total and active carbonate and plant available Fe). It can be concluded from this study that Freunglich and Langmuir equations were more suitable for describing Fe adsorption in all tested soils. Tested soils sorbed Fe according to the following arrangement: Balad > Al-Khalis > Al-Raaid > Al-Wehda > Al-Mussayib > Al-Rashidaa.